Analisis Pengaruh Kualitas Website Simojang Berdasarkan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) terhadap Kepuasan Pengguna - Muflikhatun, Martya Noor Aini; Fitrianingsih, Fitrianingsih (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Network Node Performance Monitoring Information System (SIMOJANG) is a means of monitoring, evaluating and assisting all Network Nodes in implementing the 5 pillars of geospatial information infrastructure (IIG), namely policy, institutions, human resources, standards and technology. Analysis of the quality of the SIMOJANG website is needed to improve the quality of services from SIMOJANG in the future and as feedback to determine the advantages and disadvantages of the SIMOJANG website from the user's perspective. The aim of this research is to find out whether the performance of SIMOJANG is in accordance with user expectations based on the WebQual 4.0 and Importance Performance Analysis (IPA) methods. The dimensions of website quality in this research are Usability, Information Quality and Service Interaction Quality. Respondents in this research were BIG, PPIIG, Network Nodes of Ministries/Institutions and Regional Governments (Provincial/Regency/City). Data collection was obtained from distributing online questionnaires with a sampling technique using random sampling totaling 117 respondents. The results of this research are that 58.9% of SIMOJANG quality influences user satisfaction while the remainder is influenced by variables not tested in this research. Based on the results of the performance and importance analysis (IPA), several indicators still require a lot of attention because they are in quadrant I (indicators considered important for users but their performance is still low). From these results, researchers suggest developing a website based on indicators in areas that require the most attention.